Dietary chromium supplementation for targeted treatment of diabetes patients with comorbid depression and binge eating. Issue 1 (July 2015) - Brownley, Kimberly A.; Boettiger, Charlotte A.; Young, Laura; Cefalu, William T.
Abstract Dietary chromium supplementation for the treatment of diabetes remains controversial. The prevailing view that chromium supplementation for glucose regulation is unjustified has been based upon prior studies showing mixed, modest-sized effects in patients with type 2 diabetes (T2DM). Based on chromium's potential to improve insulin, dopamine, and serotonin function, we hypothesize that chromium has a greater glucoregulatory effect in individuals who have concurrent disturbances in dopamine and serotonin function – that is, complex patients with comorbid diabetes, depression, and binge eating. We propose, as suggested by the collective data to date, the need to go beyond the "one size fits all" approach to chromium supplementation and put forth a series of experiments designed to link physiological and neurobehavioral processes in the chromium response phenotype.